Recurrent Pericarditis in Children and Adolescents - Tombetti, Enrico; Giani, Teresa; Brucato, Antonio; Cimaz, Rolando (Frontiers in Pediatrics, 2019)
Recurrent pericarditis (RP) is a clinical syndrome characterized by recurrent attacks of acute pericardial inflammation. Prognosis quoad vitam is good, although morbidity might be significant, especially in children and adolescents. Multiple potential etiologies result in RP, in the vast majority of cases through autoimmune or autoinflammatory mechanisms. Idiopathic RP is one of the most frequent diagnoses, that requires the exclusion of all known etiologies. Therapeutic advances in the last decade have been significant with the recognition of the effectiveness of anti IL1 therapy, but a correct diagnostic and therapeutic algorithm is of key importance. Unfortunately, most of evidence comes from studies in adult patients. Here we review the etiopathogenesis, diagnosis and management of RP in pediatric patients.